Experiences of Newcomers to Fransaskois Schools: Opportunities for community collaboration - Carlson Berg, Laurie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2010)
Recently, there has been an unprecedented increase in the number of Francophone immigrants to Anglo-dominant provinces in Canada. This paper presents results of an appreciative inquiry-based study into the experiences of newcomers to one Francophone community in a linguistic minority context (Saskatchewan). Transcripts of interviews with twenty-seven participants were analysed to identify potential barriers to inclusion in the Francophone school community. Recommendations are offered as to how culturally reciprocal collaboration and mentoring may be used to address identified challenges.